Transnational organised crime in international law - Obokata, Tom. (Oxford Hart Pub., 2010)
A monograph that offers a critical analysis of developments in the field of transnational organised crime under international law. It traces the history of organised crime and explores key concepts and norms relating to the practice from a multi-disciplinary perspective. It looks at legal obligations imposed upon States. There is extensive and detailed academic literature on the legal development of international crimes such as war crimes and crime against humanity. However, not much attention has been paid to other serious crimes, including narcotics-related offences, human trafficking and money laundering, which do not necessarily amount to international crimes in the traditional sense. The purpose of this monograph is to fill this gap and offer a critical analysis of developments in the field of transnational organised crime under international law. The book is divided into two parts. Part I is entitled 'Norms, Principles, and Concepts'. It traces the history of organised crime and explores key concepts and norms relating to the practice from a multi-disciplinary perspective. It then looks at legal obligations imposed upon States as well as non-State actors in relation to transnational organised crime. Part II illustrates how these norms, principles and obligations are translated and enforced in practice. This will be done through case studies at the level of national law (Thailand, Serbia and the UK), regional law (European Union) and international law (United Nations).
Introduction -- Understanding organised crime from a multi-disciplinary perspective -- Obligations of States under international law -- The role of non-state actors in suppression and prevention of organised crime -- National case studies of Thailand, Serbia, Kosovo, and the UK -- The EU and transnational organised crime -- International responses to transnational organised crime.
Keywords: Organized crime; Organized crime -- Case studies; International offenses; International offenses -- Case studies